Human immunodeficiency virus (HIV) and Human papillomavirus (HPV) infection and cell cycle regulators in preinvasive lesions and invasive carcinomas of the anus - De Jager, Louis Johann (Division of Anatomical Pathology, 2017)
Introduction: Anal cancer is a rare disease which accounts for 1.5% of gastrointestinal tract malignancies. The majority of these carcinomas are squamous cell carcinomas and are associated with high risk-HPV infection. HIV infection appears to interact synergistically with high risk-HPV in the development of squamous cell carcinoma at this site. Aims and objectives: To review the pathology of anal carcinomas and anal intraepithelial neoplasia (AIN) diagnosed between 2003 and 2012. To investigate the frequency of high risk-HPV infection and HIV infection in premalignant and malignant epithelial anal lesions using immunohistochemistry and to investigate the effect of these infections on Langerhans cell density. To investigate the role of cell cycle and WNT signalling pathway markers in the pathogenesis of these lesions. Materials and methods: This was a retrospective study and 51 cases of anal carcinoma and precursor lesions were identified during the study period. Where possible, blocks which contained normal and dysplastic tissue and invasive carcinoma were selected. Ten immunohistochemical stains (p24, p16, pRb, E-cadherin, CD1a, Langerin, Bcl-2, Ki-67, HPV L1 capsid protein and β-catenin) were performed and scored in normal, dysplastic and carcinomatous tissue. Data were analysed to determine if there were statistically significant differences in the expression of markers in different subtypes of carcinomas, grades of differentiation of carcinomas and in the range from normal to carcinoma. Results: The patients' ages ranged from 24 to 81 years. There were 26 females and 24 males; one patient did not have age or sex information available. Twenty-one cases did not have information available on HIV status. Eleven cases demonstrated squamous cell dysplasia only and 40 cases demonstrated invasive carcinoma, 36 of these being squamous cell carcinomas. p24 was positive in only two known HIVpositive cases. p16 demonstrated block positive staining in 35 out of 36 squamous cell carcinomas and 14 out of 18 high grade squamous intraepithelial lesions. There was a significant decrease in the proportion of pRb-positive cells from well to poorly differentiated squamous cell carcinomas (p=0.03). HIV status did not influence the expression of markers. The subtype of carcinoma did not have a significant effect on the proportion of pRb-positive cells. Differentiation of squamous cell carcinoma had a significant effect on the E-cadherin expression score (the more well differentiated a carcinoma, the higher the E-cadherin score; p=0.04). There was a significant difference in E-cadherin expression between normal tissue and squamous cell carcinoma, and dysplastic tissue and squamous cell carcinoma (p=0.002 and p=0.004, respectively). Differentiation, subtype of squamous cell carcinoma and HIV status did not influence the density of CD1a/Langerin-positive Langerhans cells. No significant difference in the density of CD1a/Langerin-positive cells was demonstrated amongst normal, dysplastic and squamous cell carcinoma tissue, regardless of HIV status. The differentiation, subtype of squamous cell carcinoma and HIV status, did not have a significant effect on the Bcl-2 expression. There was a significant difference in Bcl-2 expression among normal, dysplastic and cancerous tissue (p=0.02). There was no significant difference in the Ki-67 proliferation index amongst the different subtypes of squamous cell carcinoma and the degrees of differentiation. HPV L1 capsid IHC only stained two squamous cell carcinomas and nine cases with dysplastic squamous epithelium (AIN I and AIN II). There was no case which showed abnormal localisation of β-catenin. Conclusion: Less than 20% of HIV-positive cases showed positive p24 staining. p24 does not appear to be a useful stain to determine HIV status in non-lymphoid tissues. p16 is known to be a surrogate marker for high risk-HPV infection, and the fact that 35 out of 36 squamous cell carcinomas showed block positive staining suggests that the majority of squamous cell carcinomas in this study were associated with high risk-HPV infection. The mean density of CD1a- and Langerin-positive cells was increased in HIVpositive patients. HPV L1 capsid IHC showed a low sensitivity of detecting AIN and invasive SCC of the anus. Including vaccinations against high risk-HPV in the South African Expanded Programme on Immunisation may reduce the burden of anal dysplastic lesions and invasive squamous cell carcinoma in future.